A Pilot Study Evaluating Daily Physical Activity Before and After Cardiac Resynchronization Therapy. (January 2014) - Sherry, Daisy; Knight, Bradley P.; Casey, Cash; Larson, Janet; Hacker, Eileen D.; Quinn, Lauretta T.; Wang, Edward; Collins, Eileen G.
Benefits of daily physical activity are well known, but there are limited data to describe physical activity in heart failure patients who receive cardiac resynchronization therapy devices. The purpose of this pilot study was to evaluate changes in physical activity (PA) levels before and 3 months after Cardiac Resynchronization Therapy (CRT) and determine relationships of PA to physical function and comorbidities, as well as describe changes in heart failure symptoms. This was a prospective pre-/post- design that included a convenience sample of 21 subjects using self- report questionnaires and 6-minute walk test (6MWT). In this sample, there was a 2.6 hour increase in high level PA (p = 0.024). 6MW distance improved 27% (p < .0001). Subjects experienced a 25% reduction in dyspnea (p = 0.015). Knowledge gained from this study adds to the understanding of the patient response to CRT. Further study is recommended to generalize findings and explore whether an intervention (cardiac rehabilitation) is indicated.